Tendon Extracellular Matrix Alterations in Ullrich Congenital Muscular Dystrophy - Sardone, Francesca; Traina, Francesco; Bondi, Alice; Merlini, Luciano; Santi, Spartaco; Maraldi, Nadir Mario; Faldini, Cesare; Sabatelli, Patrizia (Frontiers in Aging Neuroscience, 2016)
Collagen VI is a non-fibrillar collagen expressed in skeletal muscle and most connective tissues. Mutations in collagen VI genes cause two major clinical forms, Bethlem myopathy and Ullrich congenital muscular dystrophy (UCMD). In addition to congenital muscle weakness, patients affected by collagen VI myopathies show axial and proximal joint contractures and distal joint hypermobility, which suggest the involvement of the tendon function. We examined a peroneal tendon biopsy and tenocyte culture of a 15-year-old patient affected by UCMD with compound heterozygous COL6A2 mutations. In patient's tendon biopsy, we found striking morphological alterations of tendon fibrils, consisting in irregular profiles and reduced mean diameter. The organization of the pericellular matrix of tenocytes, the primary site of collagen fibril assembly, was severely affected, as determined by immunoelectron microscopy, which showed an abnormal accumulation of collagen VI and altered distribution of collagen I and fibronectin. In patient's tenocyte culture, collagen VI web formation and cell surface association were severely impaired; large aggregates of collagen VI, which matched with collagen I labeling, were frequently detected in the extracellular matrix. In addition, metalloproteinase MMP-2, an extracellular matrix-regulating enzyme, was increased in the conditioned medium of patient's tenocytes, as determined by gelatin zymography and western blot. Altogether, these data indicate that collagen VI deficiency may influence the organization of UCMD tendon matrix, resulting in dysfunctional fibrillogenesis. The alterations of tendon matrix may contribute to the complex pathogenesis of collagen VI related myopathies.